Pengaruh Kecerdasan Emosional, Organizational Citizenship Behavior, dan Kepuasan Kerja terhadap Kinerja Karyawan - Grahandika, Guruh; Wijayati, Dewie Tri (Jurnal Ilmu Manajemen, 2021)
This study aims to determine and analyze the effect of emotional intelligence, organizational citizenship behavior and job satisfaction on employee performance at PT. Perkebunan Nusantara X Pabrik Gula Lestari Nganjuk. This research is a type with a quantitative approach with a population of 185 permanent employees, and the sampling technique uses slovin sampling with a sample of 128permanentemployees. The analytical tool used is multiple linear regression analysis by IBM SPSS 25 software. The measurement scale used is the Likert Scale. The results of the study explained that emotional intelligence significantly and positively affects employee performance. Besides that, organizational citizenship behavior has a significant and positive impact on employee performance, and job satisfaction has a significant and positive effect on employee performance. The company should maintain its performance by building a communication and work culture that has been carried out based on the values of emotional intelligence, OCB level, and employee satisfaction. In addition, it can also provide work motivation to employees in the company by providing rewards through various programs that can improve work performance and increase employee performance.